Candida albicans white and opaque cells undergo distinct programs of filamentous growth. - Haoyu Si (Public Library of Science (PLoS), 2013)
The ability to switch between yeast and filamentous forms is central to Candida albicans biology. The yeast-hyphal transition is implicated in adherence, tissue invasion, biofilm formation, phagocyte escape, and pathogenesis. A second form of morphological plasticity in C. albicans involves epigenetic switching between white and opaque forms, and these two states exhibit marked differences in their ability to undergo filamentation. In particular, filamentous growth in white cells occurs in response to a number of environmental conditions, including serum, high temperature, neutral pH, and nutrient starvation, whereas none of these stimuli induce opaque filamentation. Significantly, however, we demonstrate that opaque cells can undergo efficient filamentation but do so in response to distinct environmental cues from those that elicit filamentous growth in white cells. Growth of opaque cells in several environments, including low phosphate medium and sorbitol medium, induced extensive filamentous growth, while white cells did not form filaments under these conditions. Furthermore, while white cell filamentation is often enhanced at elevated temperatures such as 37°C, opaque cell filamentation was optimal at 25°C and was inhibited by higher temperatures. Genetic dissection of the opaque filamentation pathway revealed overlapping regulation with the filamentous program in white cells, including key roles for the transcription factors EFG1, UME6, NRG1 and RFG1. Gene expression profiles of filamentous white and opaque cells were also compared and revealed only limited overlap between these programs, although UME6 was induced in both white and opaque cells consistent with its role as master regulator of filamentation. Taken together, these studies establish that a program of filamentation exists in opaque cells. Furthermore, this program regulates a distinct set of genes and is under different environmental controls from those operating in white cells.